A Socio-Economic Study on Agroforestry in Chhachhrauli Block of Yamunanagar District of Haryana - Rai, Anil; Srivastava, A.K.; Singh, Man (Indian Journal of Agroforestry, 2020)
A survey was conducted during the first quarter of 1998 in Chhachhrauli block of Yamunanagar district of Haryana to study the contribution of farm trees on socio-economic status of the rural population. The results revealed that the families residing away from the forest boundary are getting more benefit from the agroforestry. Education has a positive role in getting the income from aqrotorestry. The adoption of agroforestry and average net annual income from agroforestry increase with increasing in holding size.